Comparative Analysis of Men’s and Women’s Cricket News in National Dailies of Bangladesh - Rashid, Mamunor; Hossain, Sara Monami; Kabir, Md. Ripul; Kabir, Nabila (South Asian Journal of Social Sciences and Humanities, 2022)
The aim of this study has been appointed to find out the ratio of women’s sports get in Bangladeshi daily newspapers, the difference in coverage of men’s and women’s cricket, and identify the overall treatment of men’s and women’s cricket news coverage during the biggest events and explore why women’s cricket news is covered in such way. Regarding this, 44 days of news from two dailies of Bangladesh have been analyzed. Interview of cricket specialists is taken to find out why they cover men’s and women’s cricket differently. This study found out that men’s cricket is covered with great excitement and during the men’s cricket world cup, most of the sports news is related to this topic. Different segments to attract readers are also published during this time. On the other hand, women’s cricket is not covered sufficiently even during the women’s T20 world cup. Men’s cricket is prioritized at this time also. Experts said that women’s cricket is not very popular among audiences and commercial purposes are the reason behind this type of coverage of women’s cricket. But the change in this type of coverage and the steps of media can make a difference in the popularization of women’s cricket in Bangladesh.